Sikap generasi muda terhadap bahasa Bali di destinasi wisata internasional Bali - Malini, Ni Luh Nyoman Seri; Yadnya, Ida Bagus Putra; Laksminy, Ni Luh Putu; Sulibra, I Ketut Ngurah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This writing aims at investigating the language attitudes of the Balinese young generation toward Balinese, their mother tongue, in tourist destinations. A qualitative approach is applied in this research. The data are in the form of spoken data, written data, and the researcher’s language intuition. Through participative observation, the data are collected from the young generation in tourist destinations such as Kuta, Sanur, and Ubud by using questionnaires and observation sheets. The respondents were given 10 question items related to cognitive, affective, and behavioral (conative) aspects. The collected data were then analyzed using language attitude theory. The study reveals that there are positive attitudes toward the Balinese language among the young generation in international tourist destinations in Bali.